Finnie's Notes on Fracture Mechanics Fundamental and Practical Lessons - Dharan, C. K. H.; Kang, B. S.; Finnie, Iain (Springer New York : Imprint: Springer, 2016)
This textbook consists primarily of notes by Iain Finnie who taught a popular course on fracture mechanics at the University of California at Berkeley. It presents a comprehensive and detailed exposition of fracture, the fundamentals of fracture mechanics and procedures for the safe design of engineering components made from metal alloys, brittle materials like glasses and ceramics, and composites. Interesting and practical problems are listed at the end of most chapters to give the student practice in applying the theory. A solutions manual is provided to the instructor. The text presents a unified perspective of fracture with a strong fundamental foundation and practical applications. In addition to its role as a text, this reference would be invaluable for the practicing engineer who is involved in the design and evaluation of components that are fracture critical. This book also: Presents details of derivations of the basic equations of fracture mechanics and the historical context of the development of fracture theory and methodology Treats linear and nonlinear fracture mechanics methodologies beginning with a review of the basic equations of solid mechanics followed by solutions useful in fracture prediction Illustrates the basis of linear elastic fracture mechanics (LEFM), practical applications of LEFM in the design of fracture-tolerant structural components Offers interesting, practical, classroom proven problems at the end of most chapters Includes instructor's solutions manual  .